Prenos dela pristojnosti v zapuščinskem postopku na notarje - Ozimek, Miha (Pravni letopis, 2008)
The paper aims to review the reasons for the adoption of the draft, amending and modifying the inheritance act, and states a critical analysis of the said draft. Owing to the established and traditional judicial probate proceeding in the Republic of Slovenia, in the opinion of the author of the paper the amendments are neither necessary nor reasonable. The act amending draft is not sufficiently upgraded from the professional point of view and generates numerous issues to which no clear answers can be given. Since the probate proceeding is initiated ex officio and considering the institute of the reference to a suit in the course of the very probate proceeding, the probate proceeding can not be subjected to the systemic and overall modification in the sense of the transfer of competence to notaries. Thus the proposed transfer of competence in the probate proceeding to notaries is only the attempt of a sort of the regulation sui generis, which will, if adopted, inevitably provide numerous lacks of precision and backlog of court cases, and most probably the proceeding will be much more high-priced.
Keywords: dedno pravo; dedovanje; notarji; pravni postopek; pristojnosti; Trusts and estates